Groundhog Oracles and Their Forebears - Capper, Daniel (Zygon, 2016)
Groundhog Day animal weather forecasting ceremonies continue to proliferate around the United States despite a lack of public confidence in the oracles. This essay probes religio-historical and original ethnographic perspectives to offer a psychological argument for why these ceremonies exist. Employing Paul Shepard's notion of a felt loss of sacred, intimate relationships with nonhuman nature, as well as Peter Homans's concept of the monument that enables mourning, this essay argues that groundhog oracles serve as monuments that allow humans experientially to attempt to heal lost sacred relationships with animals like weather forecasting bears, hedgehogs, and badgers.